Ouabain and chloroquine trigger senolysis of BRAF‐V600E‐induced senescent cells by targeting autophagy. Issue 9 (6th August 2021) - L'Hôte, Valentin; Courbeyrette, Régis; Pinna, Guillaume; Cintrat, Jean‐Christophe; Le Pavec, Gwenaëlle; Delaunay‐Moisan, Agnès; Mann, Carl; Thuret, Jean‐Yves
Abstract: The expression of BRAF‐V600E triggers oncogene‐induced senescence in normal cells and is implicated in the development of several cancers including melanoma. Here, we report that cardioglycosides such as ouabain are potent senolytics in BRAF senescence. Sensitization by ATP1A1 knockdown and protection by supplemental potassium showed that senolysis by ouabain was mediated by the Na, K‐ATPase pump. Both ion transport inhibition and signal transduction result from cardioglycosides binding to Na, K‐ATPase. An inhibitor of the pump that does not trigger signaling was not senolytic despite blocking ion transport, demonstrating that signal transduction is required for senolysis. Ouabain triggered the activation of Src, p38, Akt, and Erk in BRAF‐senescent cells, and signaling inhibitors prevented cell death. The expression of BRAF‐V600E increased ER stress and autophagy in BRAF‐senescent cells and sensitized the cell to senolysis by ouabain. Ouabain inhibited autophagy flux, which was restored by signaling inhibitors. Consequently, we identified autophagy inhibitor chloroquine as a novel senolytic in BRAF senescence based on the mode of action of cardioglycosides. Our work underlies the interest of characterizing the mechanisms of senolytics to discover novel compounds and identifies the endoplasmic reticulum stress‐autophagy tandem as a new vulnerability in BRAF senescence that can be exploited for the development of further senolytic strategies. Abstract : Cardioglycosides are particularly potent senolytics in BRAF‐V600E‐induced senescence. Senolysis by cardioglycosides is not mediated by Na, K‐ATPase pump inhibition but rather by signal transduction. BRAF‐V600E‐induced senescent cells rely on increased autophagy flux for survival. Cardioglycosides decrease autophagy flux, thus killing BRAF‐V600E‐induced senescent cells with high potency. Accordingly, autophagy inhibitor chloroquine is also senolytic in BRAF‐V600E senescence.